Cervical and endometrial cancers of intestinal origin diagnosed 18 years after vaginal replacement with a sigmoid colon segment: a case report and review of the literature - Sun, Xiao-fei; Miao, Xin-xin; Li, Bao-xuan; Wang, Yu (Frontiers in Oncology, 2022)
Background Sigmoid colpoplasty is a surgical method for the treatment of vagina agenesis. Malignant tumors of neovaginas derived from sigmoid colons are rare. Case presentation We report a 33-year-old woman who underwent sigmoid colpoplasty for vaginal agenesis and presented 18 years later with vaginal bleeding. Examination revealed cancer of the neovagina with involvement of the cervix and endometrium. The patient was administered four cycles of chemotherapy because she refused surgery. Conclusions Patients with a history of colpoplasty should undergo long-term comprehensive testing after reconstruction, including regular gynecological, colposcopic, and gastrointestinal examinations. In patients with cancer of the neovagina, a comprehensive treatment plan should be developed in consultation with gynecologists and surgeons. There is no standard treatment, although surgery plus chemotherapy or radiotherapy appears to be effective.